The influence of golf shaft stiffness on grip and clubhead kinematics - Mac Kenzie, M. J.; Boucher, D. E. (Journal of Sports Sciences, 2017)
The purpose of this study was to investigate the influence of shaft stiffness on grip and clubhead kinematics. Two driver shafts with disparate levels of stiffness, but very similar inertial properties, were tested by 33 golfers representing a range of abilities. Shaft deflection data as well as grip and clubhead kinematics were collected from 14 swings, with each shaft, for each golfer using an optical motion capture system. The more flexible shaft (R-Flex) demonstrated a higher contribution to clubhead speed from shaft deflection dynamics (P < .001), but was also associated with significantly less grip angular velocity at impact (P = .001), resulting in no significant difference in clubhead speed (P = .14). However, at the individual level, half of the participants demonstrated a significant difference in clubhead speed between shafts. The more flexible shaft was also associated with significantly different magnitudes of head rotation relative to the grip. More specifically, both bend loft (P < .001) and bend lie (P < .001) were greater for the R-Flex shaft, while bend close (P = .017) was greater for the stiffer (X-Flex) shaft. However, changes in grip orientation resulted in no significant differences in face orientation, between the shafts, at impact.